EMPLOYEES’ PERSPECTIVE ON ROBOTIC ADOPTION IN THE HOTEL BUSINESSES: SUPPORT OR STEAL JOBS FROM HUMAN? - Sadangharn, Pornrat (RMUTT Global Business and Economics Review, 2022)
This study aimed at investigating the stakeholders’ opinion toward robot adoption in the hotel businesses at the Eastern Economic Corridor (EEC). Mixed-methods research was conducted by employing a sequential exploratory strategy. Starting from a qualitative research method, thereafter, based on the findings from qualitative research, the survey questionnaire was drafted for using in the quantitative research method. Findings from the qualitative stage revealed that stakeholders in the hotel businesses at the EEC accepted the robot adoption. Factors involving in robot acceptance were human, robot, and organization. These three factors also related to the human-robot interaction. According to the survey, in quantitative findings, employees of hotels in the EEC accepted the robot at a moderate level. Regarding factors involving in robot acceptance, respondents agreed with robot factor at a high level, and agreed with organzizational factor and human factor at a moderate level. Respondents also agreed with human-robot collaboration at a high level.